INISIASI TUNAS AKSILER SERTA KALUS Toona sinensis DAN Toona sureni DENGAN SUMBER BAHAN STEK CABANG - Asri Insiana Putri; nfn Jayusman (Jurnal Pemuliaan Tanaman Hutan, 2012)
The availability of source material to multifunctional tree Toona sp. have constraints for macro and micro propagation, in this regard, this study aims to:1)observe the formation of buds on T. sinensis and T. sureni stem cuttings in an effort to sustain the availability of explants and 2)analyze the effect of GA4, IBA and BAP growth hormone on regeneration and propagation of the axillary bud initiation and callogenesis through tissue culture. Isolation of stem cuttings was conducted in a greenhouse with number of shoots per nodule and nodule distance as observed.Variables Tissue culture techniques were used to study the effect of exogenous GA4 hormones application on the initiation of axillary buds. The application of IBA hormone on plantlet rooting and callogenesis. The results showed that T. sinensis has 2-7 buds per nodule and nodule distance of 2-5 mm, while T. sureni has one bud per nodule and nodule distance of 5-10 cm. The average length of T. sinensis shoots were 15.8 cm and 17.4 for T. sureni. Enrichment with 1 mg/l GA4 gave the highest axillary shoot length on T. sinensis (8.5 cm ± 0.7228) and (9.8 cm ± 0.1022) for T. sureni. Two mg/l IBA enrichment gave the highest root length of T. sinensis (10.9 cm ± 1.8392) and for T. sureni (7.9 cm ± 0.7633). Three mg/l concentration BAP application gave the best effect in term of callus weight of T. sinensis (1.4 g ± 0.3833). Scoring of callus weight showed moderate response categories to both T. sinensis and T. sureni.